Contribution à l’étude biométrique et morpho-géométrique (méthodes de Fourrier et points homologues) de quelques espèces de concombres de mer de la côte de Mostaganem. - BELDJILALI, Mohammed; BOUOUDA, Chaabane (My University, 2020)
This work is part of the morphological, anatomical, biometric and morpho-geometric characterization of some holothurian’sspecies from the Coast of Mostaganem. Similarly, a theoretical study on two morphogeometric techniques (homologous points and Fourier 'TEF' elliptical transformations) was carried out for the aim of using them later for the identification and characterization of the endoskeleton (calcareous ring and ossicles) of these species, especially those of the genus Holothuria.
Keywords: Internal Organs; Morpho-geometry; homologous points; Fourier Transformed Ellipticals; Holothurian; Mostaganem Coast.